ARTICLE OF RELEVANCE ANALYSIS BETWEEN PILLARS OF ISLAM AND PANCASILA - Siti Habiba (JOURNAL OF LAW AND GOVERNMENT SCIENCE, 2015)
Pillars of Islam which consists of five underlying joint realization of a Muslim man to have a close connection with Pancasila, which also consists of five precepts underlying the realization of the ideal of human Indonesia. The first pillar of Islam is to say the shahadah. Testify that there is no god but Allah and Muhammad is the messenger of God. The first principle of Pancasila is the belief in one God. Indonesian Man is a man who has faith in God, and that God is worshiped, it is only one, there is no god but Allah. The second pillar of Islam is establish prayer. Second principle of Pancasila is just and civilized humanity. This means that the Indonesian people are treated fairly under the law. Prayer is a command that must be implemented by all Muslims who have legal age and understanding indiscriminately. The third pillar of Islam is zakat. Third principle of Pancasila is the unity of Indonesia. Unite the nation, unites many human means, unites hundreds of millions of people is not an easy thing, it first must unite hearts. Zakat paid by the rich to the poor will unite two hearts, the hearts of the rich and the poor heart. One key to unity is the realization of one heart. One heart embodies one word and one action that will ultimately give birth togetherness, unity and strength.  The fourth pillar of Islam is fasting. Fourth principle of Pancasila is populist, led by wisdom, wisdom in deliberation representation. In deciding the nation's problems should be discussed and decided wisely. Fasting person can abstinence and provide a fair and wise decision. The fifth pillar of Islam is the pilgrimage if it is capable of. Five precepts are social justice for all  Indonesian people. The more Muslims who went to the House, it means social justice for all Indonesian people will increasingly become apparent.Keywords: Pillars of Islam, Pancasila, Indonesia, Muslim, God